Evaluation of the Scientific Music Effect on Biochemisry Education - Aeen Sharifi; Mahdi Pouramir; Sorayya Khafri; Iman Jahanian (Babol University of Medical Sciences, 2016)
BACKGROUND AND OBJECTIVE: Music can be used in education of some fields such as: Biochemistry and Related fieldsofmolecular Biology. The question that arises here is whether the sequence, number and variety of proteins constituents could be presented via music? Our purpose has been to design and compose of music for proteins and more familiarizing the students with the first structure of them by composed music and evaluation of its role in learning the proteins structure. METHODS: This experimental study was performed on 106 persons of first semester in (2012) medical and dentistry students of Babol University of Medical Sciences. Students were divided to 2 groups containing traditional and modern education. The traditional method was performed by professor's speech and video projector and the modern method was performed by music related to first structure of the human hemoglobin type 1(HbA1). The hemoglobin music was made based on hydrophobic and hydrophilic properties of the aminoacides. At the end, a written 10-scores exam was taken from both of groups and the results were analyzed by T-Test. FINDINGS: Alpha and Beta polypeptide chains;#39 music was made and heardof the human hemoglobin. The average for the modern education group (case group) was 6.16 but for the traditional education group (control group) was 6.40. Statistically, the analysis in comparison of traditional and modern education methods of biochemistry did not show the significant differences. CONCLUSION: Although at this study, music had no affect on the result of biochemicaltests, but via music of different molecules it can be realized a difference in musical structure as a result of their biochemical structure differences.